A model of human capital of vertically integrated oil companies by creating a personnel reserve (Путеводитель предпринимателя, 2020)
The current state of Russian oil and gas industry is analyzed, the role of human capital in innovative development of the industry is described and a model of human capital formation of vertically integrated oil companies by creating a personnel reserve is developed.